Penguatan Karakter BAKU di Era Masyarakat 5.0 Pada Siswa SMK Daarut Tauhid - Mubarok, Agus; Azhim, Faiha Athiyah; Ramadhani, Hana Thufailah (International Conference on Islamic Studies, 2022)
The world is entering the era of society 5.0. some skills such as innovation, creativity, and collaboration are needed to be a solution to every problem of this era. Strengthening character is an important thing to prepare for the "Golden Generation of Indonesia 2045". Generation Z as the main actor in managing Indonesia's upcoming 2045 demographic bonus, needs to be prepared to strengthen the character of BAKU from now on. The character of BAKU which stands for "Good (Ikhlas, Honest, and Tawadhu), and Strong (Brave, Discipline, and Tough) is indispensable in the formation of a _super smart society 5.0_ for the Indonesian people. This study aims to obtain information related to the urgency and forms of character strengthening BAKU for generation Z. The method used is a qualitative method, with samples or populations taken from SMK Daarut Tauhiid with various vocational competencies and in line with era 5.0, including the fields of Accounting and Institutional Finance (female students) as well as Computer and Network Engineering, Broadcasting and Film (male students). The sample taken is 40 questionnaires, interviews, and literature studies. The results show that the urgency and form of strengthening the character of BAKU in the era of society 5.0 in generation Z are important to be optimized in all Indonesian educational institutions with the 3P concept, namely Education, Habituation, and Supervision This research is interesting to be developed so that can support the preparation of "Indonesian Golden Generation 2045".